The effects of Low-Load BFRE training on self-reported knee function and pain intensity in individuals with knee impairment - Ipavec, Matej (Annales Kinesiologiae, 2025)
Purpose: The aim of this study was to investigate the influence of low-load (LL) blood flow restriction exercise (BFRE) on orthopedic patients with knee joint injuries, focusing on the subjective assessment of knee joint function and the perception of pain in the knee joint. Methods: The participants were divided into an LL-BFRE group and a sham LL-BFRE group (SLL-BFRE). The training program to strengthen the quadriceps femoris muscle was carried out for four weeks with three training sessions per week. The LL-BFRE group trained with blood flow obstruction through the active muscles using an inflatable cuff, while the SLL-BFRE group trained without blood flow obstruction. Before and after the training program, knee joint function was assessed using the Lysholm questionnaire, and the intensity of knee pain during the training program was measured using a numerical scale. Results: In the LL-BFRE group, the exercise program did not cause a significant improvement (p = 0.359), which was from 74.1 ± 15.1 points to 79.1 ± 15.0 points (7%) in the subjective assessment of knee joint function, whereas it improved significantly (p < 0.001) by 17% from 70.8 ± 16.8 points to 82.9 ± 14.0 points in the SLL-BFRE groups. We found no significant differences in pain intensity between the LL-BFRE and SLL-BFRE groups during the training program. Conclusions: The results do not support the hypothesis that LL-BFRE exercises would lead to greater improvements in knee joint function and pain perception compared to standard exercises of the same intensity. These findings highlight the need for further research to optimize training protocols and confirm their effectiveness across diverse patient groups.